HOW TO COPE WITH BABY BLUES: A CASE REPORT - Herdian Fitria Widyanto Putri; Frilya Rachma Putri (Journal of Psychiatry Psychology and Behavioral Research, 2022)
During parturition phase, usually mother cannot get through psychological adaptations well, it can cause something that you might not accept-postpartum mental disorders called baby blues.Â  There are 30-75% of women after childbirth who experience the baby blues. Many factors affect baby blues. The symptoms that begin within a few days of delivery include mood lability, irritability, tearfulness, generalized anxiety, sleep, and appetite disturbance. The author reported a case of women with baby blues. The instrument uses Edinburgh Postnatal Depression Scale (EPDS) for screening. EPDS test on the patient showed a score of 13. The patient gets treatment with classical music therapy, a support system, and continued breastfeeding. After treatment, the patient can control her emotions, sleep well, and already breastfeed the baby. The husband also takes a role in caring for their baby. EPDS test on the patient showed a score of 8. Early detection and appropriate treatment from a midwife can decrease baby blues symptoms.Â Keywords: post-partum mental disorder, baby blues, EPDS.